2022
DOI: 10.3390/pathogens11121469
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Deep Tech to Solve Social Problems: Learning from COVID-19 mRNA Vaccine Development

Abstract: In mRNA vaccines against COVID-19, a new technology that had never been used for approved drugs was applied and succeeded in rapid clinical use. The development and application of new technologies are critical to solving emerging public health problems therefore it is important to understand which factors enabled the rapid development of the COVID-19 mRNA vaccines. This review discusses administrative and technological aspects of rapid vaccine development. In the technological aspects, I carefully examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The participation of large pharma companies was observed in some cases of viral vector and RNA-based vaccines in this analysis, demonstrating that both startups and large pharma have actively engaged in the development of vaccines using these emerging vaccine platforms. In COVID-19 vaccines, clinical development of an adenoviral vector vaccine discovered by the University of Oxford was supported by AstraZeneca and Moderna received large collaboration fees from some large pharma companies, which supported Moderna’s long-term R&D efforts [ 31 ]. Strengthening the alliance between startups and large pharma can be an option to increase the efficiency of clinical applications of new vaccine technologies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of large pharma companies was observed in some cases of viral vector and RNA-based vaccines in this analysis, demonstrating that both startups and large pharma have actively engaged in the development of vaccines using these emerging vaccine platforms. In COVID-19 vaccines, clinical development of an adenoviral vector vaccine discovered by the University of Oxford was supported by AstraZeneca and Moderna received large collaboration fees from some large pharma companies, which supported Moderna’s long-term R&D efforts [ 31 ]. Strengthening the alliance between startups and large pharma can be an option to increase the efficiency of clinical applications of new vaccine technologies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a pharmaceutical company in Japan initiated the development of a COVID-19 mRNA vaccine at approximately the same time. However, in a similar investigation, no academic articles or patents related to mRNA therapeutics were found using the same search methods, and the conduct of clinical trials involving mRNA therapeutics before the COVID-19 vaccine was not confirmed [15]. Hence, it can be inferred that there was a significant disparity in the accumulation of technological and clinical developments in mRNA therapeutics among BioNTech, Moderna, and the Japanese pharmaceutical company prior to the occurrence of COVID-19.…”
Section: Innovative Technological Development and Bio-ventures: The C...mentioning
confidence: 99%
“…Which factors enabled BioNTech and Moderna to succeed in the practical application of mRNA technologies ahead of the rest of the world? To answer this question, I analyzed published academic articles, patent filings, and clinical trials conducted by BioNTech and Moderna concerning mRNA therapeutics [15].…”
Section: Innovative Technological Development and Bio-ventures: The C...mentioning
confidence: 99%
“…Their research and development efforts over approximately ten years, from their inception to the first drug launch, were made possible by substantial funding and research support from investors, large corporations, and the government. Moderna began patent applications shortly after its founding in 2010 and had filed 90 patent applications by the end of 2019 when COVID-19 emerged [ 12 ]. They had published 44 research papers by the end of 2019, including 18 papers on foundational technology for mRNA therapeutics, twelve papers on infectious diseases (excluding COVID-19), seven papers on rare diseases, and two papers on tumors [ 12 ].…”
Section: Research and Developmental History Of Mrna And Adenoviral Ve...mentioning
confidence: 99%
“…Usually, new modality technologies used for new drugs require long-term research and development before they can be put into practical use [ 8 , 9 , 10 , 11 ]. Additionally, optimal applications are often uncertain during the early stages of technology development, requiring various research and development approaches before practical implementation [ 12 ]. Furthermore, the practical application of cutting-edge technologies significantly relies on technology transfer from universities.…”
Section: Introductionmentioning
confidence: 99%